Leishmania infection upregulates and engages host macrophage Argonaute 1, and system-wide proteomics reveals Argonaute 1-dependent host response - Moradimotlagh, Atieh; Chen, Stella; Koohbor, Sara; Moon, Kyung-Mee; Foster, Leonard J.; Reiner, Neil; Nandan, Devki (Frontiers in Immunology, 2023)
Leishmania donovani, an intracellular protozoan parasite, is the causative agent of visceral leishmaniasis, the most severe form of leishmaniasis in humans. It is becoming increasingly clear that several intracellular pathogens target host cell RNA interference (RNAi) pathways to promote their survival. Complexes of Argonaute proteins with small RNAs are core components of the RNAi. In this study, we investigated the potential role of host macrophage Argonautes in Leishmania pathogenesis. Using Western blot analysis of Leishmania donovani infected macrophages, we show here that Leishmania infection selectively increased the abundance of host Argonaute 1 (Ago1). This increased abundance of Ago1 in infected cells also resulted into higher levels of Ago1 in active Ago-complexes, suggesting the preferred use of Ago1 in RNAi in Leishmania infected cells. This analysis used a short trinucleotide repeat containing 6/GW-182 protein-derived peptide fused to Glutathione S-transferase as an affinity matrix to capture mature Ago-small RNAs complexes from the cytosol of non-infected and Leishmania-infected cells. Furthermore, Ago1 silencing significantly reduced intracellular survival of Leishmania, demonstrating that Ago1 is essential for Leishmania pathogenesis. To investigate the role of host Ago1 in Leishmania pathogenesis, a quantitative whole proteome approach was employed, which showed that expression of several previously reported Leishmania pathogenesis-related proteins was dependent on the level of macrophage Ago1. Together, these findings identify Ago1 as the preferred Argonaute of RNAi machinery and a novel and essential virulence factor by proxy that promotes Leishmania survival.